Síntese e caracterização de Surfactantes Alquil Glicosídicos derivados da amilose extraída da batata inglesa (Solanum Tuberosum L.) - França, Francisco Célio Feitosa de (2002)
Alkyl glucosides constitute a new and interesting class of surfactants, as they are biodegradable, nontoxic, and synthesized from renewable resources. These properties make them substitutes for other surfactants which are potentially damaging to the environment. The present work deals with the synthesis and characterization of two series of alkyl glucosides, which used C10, C16 and C18 alcohols as the hydrophobic part and glucose and glucose residues derived from degradation of amylose (which was essentially free from amilopectin) as hydrophilics parts. The alkyl glucosides synthesis was performed by the usual Köenigs-Knorr reaction with some modifications. The molecular structures of the surfactants were characterized by 1H, 13C nuclear magnetic resonance (NMR) together with infra-red (IR) spectroscopy. The study by NMR and IR allowed the junctions between hydrophilic head-groups and hydrophobic tailgroups to be characterized predominantly as -glycosidic. Gel permeation chromatography (GPC) showed evidences of the formation of the surfactants with five glucosides rings linked to the alkyl chain. Liquid crystals structures were investigated by the differential scanning calorimetry (DSC) technique confirming the characteristics of thermotropics properties, through the presence of double melting points. The du Noüy method was used to determine the surface-tension and critical micelle concentration (cmc) of aqueous solutions at various concentrations. For the two series of surfactants, it was observed that the increase of the alkyl chain caused the already expected decrease of cmc. The energies involved in the adsorption and micellization process calculated from the equilibrium surface tension isotherm versus ln concentration indicates co-operativety from the hydrophilics and hydrophobics grups.